Tareas académicas para promover el PLE en educación superior: perspectivas internacionales sobre diseño educativo y agencia (2023)
ABSTRACT: The concept of Personal Learning Environment (PLE) is considered as a possible lens to understand and analyse learning conditions in different educational contexts from an ecological perspective, connecting with student's agency in their learning. Previous literature shows partial approaches on how it is implemented in higher education practice, whichleave a research gap regarding how it is promoted from the learning design considering student agency. It is in this space that the present study is framed. Through a qualitative approach, semi-structured interviews have been conducted with 20 faculty members from 5 different countries, to find out about the educational tasks that promote the PLE in their courses. A sample of 34 academic tasks has been analysed through a coding system based on the learning design, the parts of the PLE and the student agency involved. The results show that the implementation of tasks for the promotion of the PLE still has room for improvement, affecting aspects of assessment, the promotion of metacognition and student self-direction. As conclusions, future lines ofwork that can be considered in practice and research on PLE are provided.